INSECTICIDE RESISTANCE ASSOCIATED WITH 2La INVERSION AND MICROSATELLITE LOCI POLYMORPHISM IN Anopheles gambiae s.s. POPULATIONS FROM LAGOS AND OYO STATES, NIGERIA (2016)
Dichlorodiphenyltrichloroethane (DDT) and deltamethrin are insecticides frequently used in malaria vector control interventions in Africa. Resistance to these insecticides has emerged in the malaria vector, Anopheles. However, the assortment of two genetic mechanisms, 2La inversion and the polymorphism of microsatellite loci, have also been associated with insecticide resistance in Anopheles populations in several countries with limited studies on these resistance mechanisms in Nigeria. This study was therefore designed to determine DDT and deltamethrin insecticide resistance, associated with 2La inversion and microsatellite loci polymorphism in Anopheles gambiae s.s. populations from Lagos and Oyo States. Larval samples of Anopheles were collected from six localities each in Lagos and Oyo States and were morphologically identified using standard methods. Emerged adult females (Lagos: n = 1,822, Oyo: n = 1,810) were exposed to 4% DDT and 0.05% Deltamethrin insecticide s separately for one hour, according to WHO insecticide susceptibility criteria . The mosquitoes were characterised using PCR and restriction enzyme digestion (for M and S forms). Resistant mosquitoes to DDT were further subjected to 2La inversion and microsatellite loci characterisation. Genotyping of DDT resistant mosquitoes to 2La inversion was performed on 30 selected Anopheles gambiae s.s. (M molecular form) from each locality using PCR. Ten microsatellite loci, selected close to documented insecticide resistance genes within and outside 2La, were examined for polymorphic alleles using standard methods. Lagos and Oyo resistant Anopheles populations were compared using descriptive statistics. The 2La inversion data for the two states were analysed using Wright F-statistic, Chi-square and Hardy-Weinberg equation. Microsatellite data were subjected to linkage disequilibrium and one-way ANOVA at α=0.05 . Mosquitoes from Lagos were more resistant to DDT and deltamethrin with 0.0-34.5 and 50.0-92.7% mortalities, respectively compared to those from Oyo with 13.3–84.0 and 80.0–100% mortalities, respectively. Significant difference in resistance profile between Lagos and Oyo Anopheles population was recorded only for DDT with deltamethrin showing insignificant values between populations. Anopheles gambiae s.s. was the only species found in all the localities surveyed in Lagos and all belonged to the M molecular form. Oyo State populations contained more Anopheles arabiensis (58.0%) than the Anopheles gambiae s.s. (42.0%) with sympatric occurrence of the M and S molecular forms. The DDT resistance profile patterned the 2La inversion karyotype (Lagos:FST=0.104; Oyo:FST=0.043) with the Chi square values falling within Hardy-Weinberg estimates (χ2=0.001-3.81, p=0.096 - 0.999) in all populations. Microsatellite genotypic linkage disequilibrium occurred in 24.0% of the loci (χ2=10.6 - 25.0, p=0.00005-0.032) between Lagos and Oyo populations. Six out of ten polymorphic alleles had significantly high genetic differentiation values, AG2H26 (FST=0.2938), AG2H175 (FST=0.0595), AG2H590 (FST=0.0519), for Lagos and Oyo populations; three of which AG2H637 (FST=0.1134), AG2H772 (FST=0.3246), AG2H143 (FST=0.0817) , were located within inversion 2La. Resistance to dichlorodiphenyltrichloroethane and deltamethrin in Anopheles population was established in Lagos and Oyo States. The resistance profile associated with 2La inversion karyotypes, and polymorphism of six microsatellite loci may be used as genetic markers in malaria vector control interventions in Lagos and Oyo States, Nigeria.